2015
DOI: 10.3758/s13414-015-0867-8
|View full text |Cite
|
Sign up to set email alerts
|

Involuntary attentional capture by task-irrelevant objects that match the search template for category detection in natural scenes

Abstract: Theories of visual search postulate that the selection of targets amongst distractors involves matching visual input to a top-down attentional template. Previous work has provided evidence that feature-based attentional templates affect visual processing globally across the visual field. In the present study, we asked whether more naturalistic, categorylevel attentional templates also modulate visual processing in a spatially global and obligatory way. Subjects were cued to detect people or cars in a diverse s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 21 publications
2
23
0
Order By: Relevance
“…Contingent attention capture was only observed for category exemplars (silhouettes of the object) or characteristic parts of the object (such as the wheels of a car or limbs of a person) but not for objects semantically related to the cued category (e.g., air freshener, car radio, bracelets, hats). These findings suggest that attentional capture in naturalistic scenes is contingent on a search template composed of visual features characterizing the target (Reeder, van Zoest, & Peelen, 2015;Evans & Treisman, 2005). Several studies have suggested that different neural structures are responsible for target and distractor processing, namely, in frontal and parietal areas, respectively.…”
Section: Introductionmentioning
confidence: 89%
“…Contingent attention capture was only observed for category exemplars (silhouettes of the object) or characteristic parts of the object (such as the wheels of a car or limbs of a person) but not for objects semantically related to the cued category (e.g., air freshener, car radio, bracelets, hats). These findings suggest that attentional capture in naturalistic scenes is contingent on a search template composed of visual features characterizing the target (Reeder, van Zoest, & Peelen, 2015;Evans & Treisman, 2005). Several studies have suggested that different neural structures are responsible for target and distractor processing, namely, in frontal and parietal areas, respectively.…”
Section: Introductionmentioning
confidence: 89%
“…These representations may be located in areas beyond the EVC yet still show coarse retinotopic specificity . A currently debated topic is whether preparatory attention can also be directed to conceptual‐level representations, such as superordinate categories like furniture or food . In the current framework, this would be possible as long as there is a set of mid‐ or high‐level shape (or texture, or color) features that characterize the category.…”
Section: Preparatory Attention Across the Visual Hierarchymentioning
confidence: 99%
“…[106][107][108][109] A currently debated topic is whether preparatory attention can also be directed to conceptual-level representations, such as superordinate categories like furniture or food. [110][111][112][113][114][115][116] In the current framework, this would be possible as long as there is a set of mid-or high-level shape (or texture, or color) features that characterize the category. For abstract categories that lack such characterizing visual features altogether, preparatory attention in the visual cortex is unlikely to be an efficient mechanism of attentional guidance.…”
Section: Goals Are Prompted By Words Indicating the Task-relevant Dimmentioning
confidence: 99%
“…The spatial modulation observed here provides a neural correlate of behavioral findings of attentional capture by objects matching a top-down category-based attentional set (Reeder and Peelen, 2013; Reeder et al, 2015). In these studies, participants searched for cars and people in natural scenes.…”
Section: Discussionmentioning
confidence: 56%
“…These tasks require spatial attention to bind features, as elegantly shown by work in neurological patients with parietal damage (Cohen and Rafal, 1991; Friedman-Hill et al, 1995). Thus, while not directly required in the current task, spatial selection may be an integral and obligatory aspect of top-down attention, even when directed to high-level categories (Wyble et al, 2013; Reeder et al, 2015).…”
Section: Discussionmentioning
confidence: 97%